Modeling and control of a three-level dual output voltage converter - Ahmed S. Hussein (2022)
The paper proposes the modeling and control of a three-level dual output voltage (TL-DOV) converter. The TL-DOV converter is mathematically modeled and incorporates the finite control set model predictive control (FCS-MPC) algorithm. Like other multilevel converters, the proposed converter also requires capacitor voltage balancing; therefore, the control objective, along with the output current control, are included in the FCS-MPC algorithm. The performance of the TL-DOV converter is validated for common and different frequencies operating conditions using MATLAB simulations. The converter can generate high quality current waveforms of different amplitude, frequency, and phase angle at two output ports independently.